Constitutive androstane receptor and pregnane X receptor cooperatively ameliorate DSS-induced colitis - Uehara, Daisuke; Tojima, Hiroki; Kakizaki, Satoru; Yamazaki, Yuichi; Horiguchi, Norio; Takizawa, Daichi; Sato, Ken; Yamada, Masanobu; Uraoka, Toshio (Digestive and liver disease, 2019)
Nuclear receptor pregnane X receptor (PXR) was shown to be protective in case of dextran sulfate sodium (DSS)-induced colitis. Constitutive androstane receptor (CAR) belongs to the same nuclear receptor subfamily with PXR. The roles of both receptors in DSS-induced colitis were evaluated. Wild-type, Car-null, Pxr-null, and Car/Pxr-null mice were treated with a CAR/PXR agonist or vehicle and administered 2.5% DSS in the drinking water. The typical clinical symptoms, histological scoring, proinflammatory cytokine, and apoptosis were analyzed. Mice treated with the PXR agonist pregnenolone-16α-carbonitrile (PCN) were protected from DSS-induced colitis, as in a previous study. Mice treated with the CAR agonist, 4-bis[2-(3,5-dichloropyridyloxy)]benzene (TCPOBOP) were also protected from DSS-induced colitis. Interestingly, the protective effects of PCN in the Car-null mice and those of TCPOBOP in the Pxr-null mice both decreased. PCN or TCPOBOP pretreatment significantly decreased the macrophage and monocyte infiltration in DSS-induced colitis. PXR and CAR agonists reduced the mRNA expression of several proinflammatory cytokines in a PXR- and CAR-dependent manner, respectively. CAR inhibited apoptosis by inducing Gadd45b. PXR inhibited TNF-α and IL-1b and CAR induced Gadd45b in in vitro cell analyses. We showed that CAR and PXR cooperatively ameliorate DSS-induced colitis. PXR and CAR protected against DSS-induced colitis by inhibiting proinflammatory cytokines and apoptosis, respectively.